Interhemispheric asymmetry of uncertainties in the ionosphere-thermosphere system - Zhan, Weijia (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionThe north-south difference, or interhemispheric asymmetry (IHA), in the ionosphere-thermosphere (IT) system serves as an indicator of the complex responses to various asymmetric factors between the Northern and Southern Hemispheres. While previous studies have documented IHA in multiple parameters—such as polar plasma convection, neutral wind, and field-aligned currents—little attention has been given to the asymmetric behaviors of uncertainties or variability in these parameters. A comprehensive study of these uncertainties could provide deeper insights into the impacts of source factors on the IT system.MethodsIn this study, we build upon prior work on quantifying uncertainties in the IT system using the Whole Atmosphere Model-Ionosphere-Plasmasphere Electrodynamics (WAM-IPE) simulations and a polynomial chaos expansion-based uncertainty quantification (UQ) framework. Our focus shifts to the IHA of uncertainties in the IT system. Specifically, we present the uncertainties of electron density, plasma drifts and neutral winds obtained by applying uncertainty representation and propagation methods to the WAM-IPE model under moderately quiet conditions.Results and discussionThe estimated uncertainties exhibit clear north-south asymmetry in the mid-to-high-latitude regions, with the asymmetry sometimes reversing at different times. A prominent feature is that uncertainties in plasma density, plasma drifts, and neutral winds show larger enhancements or broader distributions in the Southern Hemisphere. Vertical variations of IHA in plasma density are also observed, with larger values at lower altitudes (250 km) across most universal and local times, and at 300 km in the Southern Hemisphere at specific local times. While north-south asymmetry in electron density, plasma drifts, and neutral winds at mid-to-high latitudes has been previously reported, this study is the first to reveal the asymmetric uncertainties in the mid-to-high-latitude ionosphere. We offer potential explanations for these distinctive features, although further theoretical analyses are necessary to understand the underlying mechanisms better.